1983
DOI: 10.4141/cjas83-090
|View full text |Cite
|
Sign up to set email alerts
|

Stage of Lactation Effects, Repeatabilities and Influences on Weaning Weights of Yield and Composition of Milk in Beef Cattle

Abstract: MoNonecor, I., WrlroN, J. W., Ar-r-eN, O. B. eNo SoNc, H. 1983. Stage of lactation effects, repeatabilities and influences on weaning weights of yield and composition of milk in beef cattle. Can. J. Anim. Sci. 63: 751-761. Yield and composition of milk was measured on 270 cows with up to three parities each. Several combinations of breeds were included with all first parity females nursing Angus-sired calves and second and third parity females nursing Simmental-sired calves. Milk yields and compositions were o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
16
1
6

Year Published

1990
1990
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 5 publications
5
16
1
6
Order By: Relevance
“…The Brandon results were consistent with the findings of Mondragon et al (1983), where they reported that cow weight had no effect on milk yield, while fatter cows produced less milk. The Manyberries results are in agreement for the relationship of cow fat and milk yield but not for cow weight and milk yield.…”
Section: Methodssupporting
confidence: 82%
See 1 more Smart Citation
“…The Brandon results were consistent with the findings of Mondragon et al (1983), where they reported that cow weight had no effect on milk yield, while fatter cows produced less milk. The Manyberries results are in agreement for the relationship of cow fat and milk yield but not for cow weight and milk yield.…”
Section: Methodssupporting
confidence: 82%
“…Robison et al (1978), Lawson (1981), Mondragon et al (1983), and Butson and Berg (1984a,b) reported that milk protein percentage increased over periods. Lawson (1981) and Butson and Berg (1984a,b) PT and SNF by periods.…”
Section: Methodsmentioning
confidence: 99%
“…Milk production was recorded on days 0, 14, 21, and 35 from the beginning of supplementation, using a portable milking machine according to the method described by Mondragon et al (1983). In the morning, after cows received their meal, calves were separated and the udder was emptied using 20 IU of oxytocin i/m (Neurofisin, Lab Fatro, Uruguay).…”
Section: Methodsmentioning
confidence: 99%
“…Aparentemente, existe um padrão geral de declínio na produção de leite durante a lactação que seria dependente do regime alimentar (MONDRAGON et al, 1983). Nas raças Canchim e Nelore, ALENCAR et al (1988) observaram queda linear da produção de leite com a progressão da lactação.…”
Section: Introductionunclassified